S08-3: Closing a Gap in Physical Activity Policy Monitoring: The Development of a Tool for the Early Childhood Education and Care Setting (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: A recently published systematic review has shown that public policies have the potential to change the physical activity (PA) environment in the early childhood education and care (ECEC) setting and to positively influence the PA behaviour of preschool children. However, established PA policy monitoring tools primarily focus on the school setting and usually do not collect data on ECEC policies. At the same time, in Germany a working group of the Supreme Health Authorities of the Federal States agreed upon a set of health indicators, which includes the policy of promoting PA in ECEC. To address this gap, a monitoring tool was developed to assess the content of ECEC policies at the subnational level, thus supporting intersectoral monitoring across the health and education sectors.Methods: The tool was developed in a five-step process: (1) a content analysis of the educational framework plans of all 16 German states, (2) a systematic review of the effectiveness of PA promotion policies in the ECEC setting, (3) an analysis of national and international policy recommendations on PA promotion in the ECEC setting, (4) a two-stage Delphi survey with 26 policymakers, researchers, and practitioners, and (5) pilot testing conducted by the health reporting departments from three State Ministries of Health in Germany.Results: The prefinal version of the tool consists of 28 items to assess the policy content of state-level educational framework plans. The items are structured around eight themes: (1) intersectoral development of educational framework plans, (2) dedicated chapter on PA, (3) pedagogical concept, (4) education-related objectives, (5) outdoor PA opportunities, (6) indoor PA opportunities, (7) stakeholder involvement, and (8) implementation of measures. Following pilot testing, adaptations were made to improve the tool’s usability. The tool includes a point scoring system to facilitate an assessment of educational framework plans within the German public health reporting system.Conclusions: The tool closes a gap in the PA policy monitoring landscape by focusing on the ECEC setting. While it has the potential to support intersectoral collaboration between the health and education sectors in Germany, its applicability and transferability to other countries need to be further explored.